Implementation of solutions for distributed team management in IT sector companies - Kuzyk, Mykhailo; Miłosz, Elżbieta (Journal of Computer Sciences Institute, 2020)
The article presents the results of a comparative analysis of selected IT tools supporting the management of a distributed IT team in companies from the IT sector. The research was carried out using two methods: scientific experiment (implementation of a test project in the tested tools) and comparative analysis (assessment of tools from the side of management and contractors of a distributed team according to the proposed criteria). The research results were aimed at choosing the best solutions that could be implemented to manage a distributed team in IT sector companies.